LF Bracketing Paradoxes: A New Account. (1st December 2018) - Belk, Zoë
Abstract: Modified noun phrases like heavy drinker and hard worker show many of the same properties as bracketing paradoxes like nuclear physicist, but they seem to differ from the latter examples in important ways. This article argues that hard worker –type phrases should be analyzed as bracketing paradoxes where the syntactic structure is isomorphic to the PF structure, unlike nuclear physicist –type examples, where syntax and LF are isomorphic. I propose that hard worker –type paradoxes, or LF bracketing paradoxes, result from a process of rebracketing at LF, which can be seen as a type of movement. This movement, and indeed all movement, is constrained by a principle of Information Preservation, which ensures that certain aspects of structural information are not destroyed during movement. The result is an analysis that accurately captures the facts about bracketing paradoxes of both types in English and Dutch.